Effectiveness of Continuous Cardiac Rehabilitation after Coronary Artery Bypass Grafting - Kobayashi, Taira; Murakami, Yoshiaki; Honma, Tomoaki; Ueda, Masami; Hamamoto, Masaki (Nihon Kanshikkan Gakkaishi, 2019)
Objective: The objective of this study was to evaluate the effectiveness of continuous cardiac rehabilitation after coronary artery bypass grafting (CABG). Method: We surveyed 107 patients about six months after isolated CABG from January 2010 to June 2015 in our hospital. Result: Cardiac rehabilitation was maintained in 57 patients (53%) (CR group). 50 patients self-suspended cardiac rehabilitation (NCR group). During a mean (±SD) follow-up of 42 ± 18 months, 15 patients died. The 3-year survival rate in the CR group was 98% versus 88% in the NCR group (p=0.09). Cardiac events occurred in 20 patients. The 3-year cardiac event-free rate was 95% for the CR group versus 79% for the NCR group (p=0.02). Conclusion: Continuous cardiac rehabilitation might improve the prognosis of the patients after coronary artery bypass grafting.